Two negatives make a positive so, -13 - (-49) equals -13 + 49, or 49-13, they are all the same thing, all equal to 36.
Answer:
f(n) = 2 + 5n. This is an arithmetic sequence.
Step-by-step explanation:
f(1) = 7
f(2) = 7 + 5
f(3) = 7 + 5 + 5 = 7 +10
f(4) = 7 + 5 + 5 + 5 = 7 + 15
In general,
f(n) = 7 + 5(n -1 )
= 7 + 5n - 5
= 2 + 5n
We have the sequence 7, 12, 17, 22, 27 …
This is an arithmetic sequence, because it is a sequence of numbers in which the <em>common difference</em> between consecutive terms is 5.
10) 7(2m+3)
11) 3(3r-1)
12) 2p(5q+4)
There are two negative roots to the provided polynomial function
f(x) = x⁷ – 2x⁴ + 7x² + 2x – 2
<h3>What is polynomial?</h3>
Polynomial is the combination of variables and constants systematically with "n" number of power in ascending or descending order.
We have a polynomial function:
f(x) = x⁷ – 2x⁴ + 7x² + 2x – 2
Using the zero product property:
After solving:
x = -1, x = -0.853, and x = 0.418 (using the graph method)
Thus, there are two negative roots to the provided polynomial function
f(x) = x⁷ – 2x⁴ + 7x² + 2x – 2
Learn more about Polynomial here:
brainly.com/question/17822016
#SPJ1
Answer:
69
Step-by-step explanation: